(untitled) (KULT_online, 2009)
In this volume German scholar Philipp Theisohn addresses the much scandalised and tabooed phenomenon of plagiarism. His "unoriginal literary history" of 14 chapters presents both general causes and conditions of intellectual property rights violation and specific examples thereof, and encompasses ideo-historical phases from antiquity to the digital age with its ’copy/paste’ practices. Alongside a thorough investigation of the plagiarist crime scene, the reader is also granted rare insight into the forms and effects of ’unethical’ literary production, the fundamental disposition of the cultural industry, the significance of medial transformations, and the self-perception of all parties involved.